حساب الأعطال البسيطة في الشبكات الكهربائية باستخدام نموذج رياضي عام - شرم أحمد (Latakia University Journal -Engineering Sciences Series, 2019)
يتناول البحث دراسة وحساب الأعطال الكهربائية المتناظرة وغير المتناظرة في الشبكات الكهربائية البسيطة. كما تم وضع واستخدام نموذج عام بالصيغة المصفوفية لمعادلات المركبات المتناظرة للجهود عند عقدة العطل والشروط الحدية لنوع العطل المدروس بغية الحصول على قيم المركبات المتناظرة لتيارات العطل. ووضع خوارزمية حساب وبرنامج حل لها، لأي عطل كهربائي عند أي عقدة دون معالجة الشبكة من بدايتها، ودون الحاجة إلى تشغيل البرنامج مرة أخرى عند تغير عقدة العطل أو نوعه في الشبكة نفسها. تم إعداد برنامجٍ حاسوبيٍ للالغوريتم المذكور وتطبيقه على شبكة نموذجية، وتم الحصول على جميع قيم المركبات المتناظرة للجهود في عقد الحمولة وكذلك للتيارات في عقد العطل والتوليد أثناء حدوث أي عطل بسيط في أي عقدة من عقد الشبكة. This research studies and calculates simple electrical faults "symmetric and asymmetric", in the electrical networks, using general algorithm to calculate electrical networks during fault occurrence. A general model in matrix equations formula of symmetric volts components in fault’s node and the ultimate conditions of each fault’s type has been set, in order to obtain symmetric components values of fault’s currents at faults node where fault is being studied without the need to re-run the program once again when changing fault node or fault type at the same network. A program for the mentioned algorithm is set and applied on typical electrical network so all symmetric components values of volts at load nodes and that is the case for currents at fault and generation nodes during any simple fault occurrence at any node of network.